The feasibility of mixed reality-based upper extremity self-training for patients with stroke—A pilot study - Ham, Yeajin; Yang, Dong-Seok; Choi, Younggeun; Shin, Joon-Ho (Frontiers in Neurology, 2022)
Mixed reality (MR), which combines virtual reality and tangible objects, can be used for repetitive training by patients with stroke, allowing them to be immersed in a virtual environment while maintaining their perception of the real world. We developed an MR-based rehabilitation board (MR-board) for the upper limb, particularly for hand rehabilitation, and aimed to demonstrate the feasibility of the MR-board as a self-training rehabilitation tool for the upper extremity in stroke patients. The MR-board contains five gamified programs that train upper-extremity movements by using the affected hand and six differently shaped objects. We conducted five 30-minute training sessions in stroke patients using the MR-board. The sensor measured hand movement and reflected the objects to the monitor so that the patients could check the process and results during the intervention. The primary outcomes were changes in the Box and Block Test (BBT) score, and the secondary outcomes were changes in the Fugl–Meyer assessment and Wolf Motor Function Test (WMFT) scores. Evaluations were conducted before and after the intervention. In addition, a usability test was performed to assess the patient satisfaction with the device. Ten patients with hemiplegic stroke were included in the analysis. The BBT scores and shoulder strength in the WMFT were significantly improved (p < 0.05), and other outcomes were also improved after the intervention. In addition, the usability test showed high satisfaction (4.58 out of 5 points), and patients were willing to undergo further treatment sessions. No safety issues were observed. The MR-board is a feasible intervention device for improving upper limb function. Moreover, this instrument could be an effective self-training tool that provides training routines for stroke patients without the assistance of a healthcare practitioner.